Waterfalls Partial Aggregation in Wireless Sensor Networks. (23rd May 2016) - Li, Wuyungerile; Jia, Bing; Saruwatari, Shunsuke; Watanabe, Takashi
Abstract : In wireless sensor networks (WSNs), energy saving is a critical issue. Many research works have been undertaken to save energy. Data aggregation is one of the schemes that save energy by reducing the amount of data transmission. Normally, researchers focus on saving energy by aggregating multiple data or turning to achieving short transmission delay in data aggregation; few of them are concerned with network lifetime. This work achieves an optimum network lifetime by balancing energy consumption among nodes in network. Here, we propose a waterfalls partial aggregation, controlled by a set of waterfalls pushing rate vectors. The first contribution of this paper is to propose a waterfalls partial aggregation and to model it with queuing theory. The second contribution is that the optimum network lifetime is achieved mathematically and a near optimum algorithm is proposed for a given transmission delay. The results are compared with existing energy efficient algorithms and the evaluation results show the efficiency of proposed algorithm.